Density functional theory simulation of the deoxygenation of lignite model compounds in the aqueous phase under a CO atmosphere catalyzed by OH− ions. (28th March 2022) - Zheng, Qing; Wang, Huhu; Peng, Wencai; Zhang, Jianshu; Zhang, Jinli; Tong, Yanbin; Li, Jun
Abstract : The most probable active H species (H − ) in the CO–OH − system and the catalytic cycle of OH − in this process were identified. Abstract : In this paper, the mechanism of the deoxygenation of lignite model compounds in the aqueous phase under a CO atmosphere catalyzed by OH − ions was investigated at the M06-2X/6-311++G(d, p) level. The results revealed that for the deoxygenation of phenol, the activity of the H species follows H˙ > H − > H +, and the reaction of CO with OH − ions under aqueous conditions confirmed that H − is the dominating active species. The study of H − attacking carbon atoms at different positions on phenol indicated that deoxygenation via substitution to form benzene is preferred over hydrogenation via addition. The effect of the active species H − on the deoxygenation of the lignite model compounds phenol, benzenediols, and benzenetriols was also examined. This study provides valuable information for future research on lignite deoxygenation.